Deleterious effects of diatom-derived polyunsaturated aldehydes on early life stages of a marine forage fish - Jiho Kim; Morgan E. Eisenlord; W. James Cooper; Karin L. Lemkau; Matthew Zinkgraf; Joy Cobb; Galexie Clelland; M. Brady Olson (Journal of Experimental Marine Biology and Ecology, 2026)

The Arlington study of healthy aging: a multidisciplinary community cohort study of functional decline with age - Delaney L. Davis; Rajvi Shah; Logan Pixler; Dang M. Mai; Juliana Santos; Camille Chandler; Kendall White; Jennifer Nguyen; Ario S. Moradi; Javed Choudhari; Carrie Arena-Marshall; Chase Johnson; et al. (GeroScience, 2026)

The first documented volcanic eruption of Hayli Gubbi, Afar, Ethiopia - Dereje Ayalew; Karen Fontijn; Faysel Sefa Abdu; Derek Keir; Amdemichael Z. Tadesse; Carolina Pagli; Alessandro La Rosa; Pablo Tierz; Abate Melaku; William Hutchison; Patrick Sugden; Gezahegn Yirgu; et al. (Bulletin of Volcanology, 2026)
Hayli Gubbi volcano in the Afar Regional State of Ethiopia experienced its first historically documented volcanic eruption on 23 November 2025. The event produced a short-lived sustained eruption column, with ash dispersal and fallout primarily towards the north and east of the volcano, and the formation of two new craters at Hayli Gubbi’s summit. Ash from the northern lobe has a basaltic (trachy)andesitic composition. The eruption was preceded, in July 2025, by a dyke intrusion originating from neighbouring Erta Ale volcano, migrating over 30 km southward and intercepting Hayli Gubbi where inflation occurred. Renewed ground deformation started again in Erta Ale ~ one month before the Hayli Gubbi eruption during which a sudden reservoir contraction and a new collapse caldera was formed. Synchronous deformation signals suggest both volcanoes are structurally coupled. Intense degassing continues at Hayli Gubbi during the months after the eruption. We provide the first accounts of the eruption’s development, assembling on-the-ground observations, geophysical and geochemical data and satellite imagery to characterize the physical features of the eruption and its impact. Whilst impact remained limited, partly due to low exposure in the remote region, the eruption did cause disruption to international air traffic. This eruption is another stark reminder of the urgent need for increased capacity for volcano monitoring and data-supported volcanic hazard assessment in Ethiopia.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Examining the ‘Consumer Repair Journey’ and Business Intervention Opportunities to Enhance Customer Experience and Satisfaction - Tung Dao; Tim Cooper; Matthew Watkins (Circular Economy and Sustainability, 2026)
The current linear economic model has led to the creation of low-priced and short-lived products at the cost of shaping fast and unsustainable consumption. Product repair, the process of maintaining the functionality of items by correcting a defect, should, in theory, retain product value and improve material efficiency. However, the transformation of current repair practices requires the comprehensive engagement of consumers and different business stakeholders, including manufacturers, retailers and repair service providers. In particular, the repair journey that consumers go through when deciding whether (and how) to repair an item involves a set of complex decisions and actions. This paper aims to provide a synthesis of this sequence and address the complexity of the consumer’s repair journey, considering different product sectors. To achieve this aim, the research consisted of a set of consumer focus groups to gather insights into consumers’ repair journeys, considering four stages: identification of product faults and repair need, information search and evaluation of alternatives, repair in action and post-repair evaluation. The paper contributes to the field by developing a holistic ‘consumer repair journey’ framework and presents findings on the factors that influence consumer intentions, how these intentions translate into behaviour at each stage, and overall satisfaction during the journey. Additionally, it provides guidance to industry professionals on how to implement interventions that could positively impact consumer repair intentions and their translation into behaviour. These interventions could align with companies’ strategic efforts to embrace customer experience, ‘right to repair’ initiatives, and the growth of sustainable, repair-focused enterprises across various product industries, as advocated by the European Commission (2020) and, more recently, Right to Repair Europe (2023).

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Updated genetic testing in individuals with unexplained adenomatous polyposis and the diagnostic yield - Blake Rowell; Maegan E. Roberts; Pamela L. Brock; Julia Cooper; Rachel Pearlman; Matthew F. Kalady; Stacey Culp; Peter P. Stanich; Josie Baker (Familial Cancer, 2025)

Late Quaternary inundation and desiccation of Megalake Chad traced in dust records from the Equatorial Atlantic Ocean - Anya J. Crocker; Christopher W. Kinsley; Amy M. Jewell; Paul S. Breeze; Nicholas A. Drake; David McGee; Charles S. Bristow; Katie Manning; Claudia Di Biagio; Paola Formenti; William R.C. Burton; Annie L. Murray; et al. (Quaternary Science Reviews, 2025)

Tracking long-term benthic recovery at a disused marine aggregate extraction site using monitoring tools developed for the marine aggregate industry - Paul S.O. McIlwaine; Peter J. Barry; Matthew Curtis; Keith M. Cooper (Estuarine, Coastal and Shelf Science, 2025)

Multiple episodes of serpentinite alteration revealed by progressive leaching experiments - Aled D. Evans; Matthew J. Cooper; Dave Craw; Damon A.H. Teagle (Geochimica et Cosmochimica Acta, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Critical assessment of missense variant effect predictors on disease-relevant variant data - Ruchir Rastogi; Ryan Chung; Sindy Li; Chang Li; Kyoungyeul Lee; Junwoo Woo; Dong-Wook Kim; Changwon Keum; Giulia Babbi; Pier Luigi Martelli; Castrense Savojardo; Rita Casadio; et al. (Human Genetics, 2025)
Regular, systematic, and independent assessments of computational tools that are used to predict the pathogenicity of missense variants are necessary to evaluate their clinical and research utility and guide future improvements. The Critical Assessment of Genome Interpretation (CAGI) conducts the ongoing Annotate-All-Missense (Missense Marathon) challenge, in which missense variant effect predictors (also called variant impact predictors) are evaluated on missense variants added to disease-relevant databases following the prediction submission deadline. Here we assess predictors submitted to the CAGI 6 Annotate-All-Missense challenge, predictors commonly used in clinical genetics, and recently developed deep learning methods. We examine performance across a range of settings relevant for clinical and research applications, focusing on different subsets of the evaluation data as well as high-specificity and high-sensitivity regimes. Our evaluations reveal notable advances in current methods relative to older, well-cited tools in the field. While meta-predictors tend to outperform their constituent individual predictors, several newer individual predictors perform comparably to commonly used meta-predictors. Predictor performance varies between high-specificity and high-sensitivity regimes, highlighting that different methods may be optimal for different use cases. We also characterize two potential sources of bias. Predictors that incorporate allele frequency as a predictive feature tend to have reduced performance when distinguishing pathogenic variants from very rare benign variants, and predictors trained on pathogenicity labels from curated variant databases often inherit gene-level label imbalances. Our findings help illuminate the clinical and research utility of modern missense variant effect predictors and identify potential areas for future development.

Metabolic Profiles of Encapsulated Chondrocytes Exposed to Short-Term Simulated Microgravity - Annika R. Bergstrom; Matthew G. Glimm; Eden A. Houske; Gwendolyn Cooper; Ethan Viles; Marrin Chapman; Katherine Bourekis; Hope D. Welhaven; Priyanka P. Brahmachary; Alyssa K. Hahn; Ronald K. June (Annals of Biomedical Engineering, 2025)
The mechanism by which chondrocytes respond to reduced mechanical loading environments and the subsequent risk of developing osteoarthritis remains unclear. This is of particular concern for astronauts. In space the reduced joint loading forces during prolonged microgravity (10 −6 g) exposure could lead to osteoarthritis (OA), compromising quality of life post-spaceflight. In this study, we encapsulated human chondrocytes in an agarose gel of similar stiffness to the pericellular matrix to mimic the cartilage microenvironment. We then exposed agarose-chondrocyte constructs to simulated microgravity (SM) for four days using a rotating wall vessel (RWV) bioreactor to better assess the cartilage health risks associated with spaceflight. Metabolites extracted from media and agarose gel constructs were analyzed on liquid chromatography-mass spectrometry. Global metabolomic profiling detected a total of 1205 metabolite features, with 497 significant metabolite features identified by ANOVA (FDR-corrected p -value 3 , and aminosugars metabolism identified by variable importance in projection scores. Microgravity-induced metabolic shifts in gel constructs and media were indicative of protein synthesis, energy and nucleotide metabolism, and oxidative catabolism. Microgravity associated-metabolic shifts were consistent with our previously published early osteoarthritic metabolomic profiles in human synovial fluid, suggesting that even short-term exposure to microgravity (or other reduced mechanical loading environments) may lead to the development of OA. This work further suggests the potential to detect these metabolic perturbations in synovial fluid in vivo to ascertain osteoarthritis risk in astronauts.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Corrigendum to “Physical workplaces and human well-being: A mixed-methods study to quantify the effects of materials, windows, and representation on biobehavioral outcomes” [Building and Environment 224 (2022) 109516] - Isabella P. Douglas; Elizabeth L. Murnane; Lucy Zhang Bencharit; Basma Altaf; Jean Marcel dos Reis Costa; Jackie Yang; Meg Ackerson; Charu Srivastava; Michael Cooper; Kyle Douglas; Jennifer King; Pablo E. Paredes; et al. (Building and Environment, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

*Inactivation of encysted muscle larvae of Trichinella spiralis in pigs using Mebendazole - Jorrell Fredericks; Dolores E. Hill; Dante S. Zarlenga; Valsin M. Fournet; Diane S. Hawkins-Cooper; Joseph F. Urban; Matthew Kramer (Veterinary Parasitology, 2024)

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

Development of a culturally targeted chatbot to inform living kidney donor candidates of African ancestry about APOL1 genetic testing: a mixed methods study - Elisa J. Gordon; Jessica Gacki-Smith; Matthew J. Gooden; Preeya Waite; Rochell Yacat; Zenab R. Abubakari; Debra Duquette; Akansha Agrawal; John Friedewald; Sarah K. Savage; Matthew Cooper; Alexander Gilbert; et al. (Journal of Community Genetics, 2024)
Clinical chatbots are increasingly used to help integrate genetic testing into clinical contexts, but no chatbot exists for A polipoprotein L1 ( APOL1 ) genetic testing of living kidney donor (LKD) candidates of African ancestry. Our study aimed to culturally adapt and assess perceptions of the Gia® chatbot to help integrate APOL1 testing into LKD evaluation. Ten focus groups and post-focus group surveys were conducted with 54 LKDs, community members, and kidney transplant recipients of African ancestry. Data were analyzed through thematic analysis and descriptive statistics. Key themes about making Gia culturally targeted included ensuring: (1) transparency by providing Black LKDs’ testimonials, explaining patient privacy and confidentiality protections, and explaining how genetic testing can help LKD evaluation; (2) content is informative by educating Black LKDs about APOL1 testing instead of aiming to convince them to undergo testing, presenting statistics, and describing how genetic discrimination is legally prevented; and (3) content avoids stigma about living donation in the Black community. Most agreed Gia was neutral and unbiased (82%), trustworthy (82%), and words, phrases, and expressions were familiar to the intended audience (85%). Our culturally adapted APOL1 Gia chatbot was well regarded. Future research should assess how this chatbot could supplement provider discussion prior to genetic testing to scale APOL1 counseling and testing for LKD candidate clinical evaluation.

Bioaccumulation of mercury in Lake Michigan painted turtles (Chrysemys picta) - Alison M. Zachritz; Katherine E. O’Reilly; Dayna L. Smith; Matthew J. Cooper; Karl M. Schlaht; Gary A. Lamberti (Environmental Monitoring and Assessment, 2024)

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Does site selection need to be democratized? A case study of grid-tied microgrids in Australia - Pierrick Chalaye; Bjorn Sturmberg; Hedda Ransan-Cooper; Kathryn Lucas-Healey; A. Wendy Russell; Johannes Hendriks; Paula Hansen; Matthew O'Neill; Warwick Crowfoot; Phil Shorten (Energy Policy, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

An adaptable integrated modelling platform to support rapidly evolving agricultural and environmental policy - Paula A. Harrison; Kate Beauchamp; Joe Cooper; Ian Dickie; Alice Fitch; Richard Gooday; Michael Hollaway; Ian P. Holman; Merryn Hunt; Laurence Jones; Thomas Mondain-Monval; Daniel Sandars; et al. (Environmental Modelling & Software, 2023)

Dietary Habits of Hardhead (Ariopsis felis) and Gafftopsail (Bagre marinus) Catfish Revealed through DNA Barcoding of Stomach Contents - Ana R. Osowski; Matthew B. Jargowsky; Pearce T. Cooper; Sean P. Powers; J. Marcus Drymon (Fishes, 2023)
A better understanding of trophic interactions between hardhead catfish (Ariopsis felis) and gafftopsail catfish (Bagre marinus) is crucial for developing multi-species management strategies for the northern Gulf of Mexico (GOM). These two species are often aggregated in food web models; however, limited data are available to substantiate this approach. Therefore, the present study aimed to describe the dietary habits of hardhead catfish and gafftopsail catfish using analysis of stomach contents aided by DNA barcoding. Hardhead (n = 693) and gafftopsail (n = 655) catfish were sampled in the northern GOM from 2015–2019 using both fisheries-dependent and -independent techniques. The average percent number (%N), average percent mass (%M), prey specific number (%PN), prey specific mass (%PM), and prey-specific index of relative importance (%PSIRI) were computed to quantify prey species. The stomach content analysis identified distinct differences in diet between hardhead and gafftopsail catfish. Crustaceans were the most important prey for hardhead catfish, while gafftopsail catfish showed a significantly broader dietary breadth and were primarily piscivorous. Multivariate analyses indicated that the location of capture explained the greatest amount of diet variability for both species. These findings address fundamental knowledge gaps regarding the dietary habits of hardhead and gafftopsail catfish in northern GOM ecosystems.

The history of ice-sheet retreat on North America during Termination 5: Implications for the origin of the sea-level highstand during interglacial stage 11 - Rebecca L. Parker; Gavin L. Foster; Marcus Gutjahr; Paul A. Wilson; Stephen P. Obrochta; Nathalie Fagel; Matthew J. Cooper; Agnes Michalik; James A. Milton; Ian Bailey (Earth and Planetary Science Letters, 2023)

Tidal barriers and fish – Impacts and remediation in the face of increasing demand for freshwater and climate change - Christopher M. Bice; Jeroen Huisman; Matthew E. Kimball; Martin Mallen-Cooper; Brenton P. Zampatti; Bronwyn M. Gillanders (Estuarine, Coastal and Shelf Science, 2023)

Fecundity trends of Chinook salmon in the Pacific Northwest - Michael J. Malick; James P. Losee; Gary Marston; Mickey Agha; Barry A. Berejikian; Brian R. Beckman; Matthew Cooper (Fish and Fisheries, 2023)
Fecundity is an important demographic parameter that contributes to the productivity of anadromous fish stock dynamics. Yet, studies on fecundity patterns in Pacific salmon ( Oncorhynchus spp.) often only include a few years of data, limiting our ability to understand spatio‐temporal trends. Here, we used data on 43 hatchery Chinook salmon ( O . tshawytscha , Salmonidae) populations in Washington State to evaluate whether average fecundity changed over the past three decades. We then used data from a subset of stocks (18) to evaluate the relationship between fecundity and body length. Our results revealed significant changes in fecundity across the 25‐year study period with most stocks showing declines in fecundity over the past decade. Results further showed that Chinook salmon have decreased in length over this same period and that annual variation in mean length explains a majority (62%) of annual variation in mean fecundity. Specifically, we estimated that a 1‐mm reduction in length results in 7.8 fewer eggs (95% CI = 6.6–8.9). Given that the majority of Pacific Northwest Chinook salmon in the environment and harvested in fisheries originate from hatchery releases and that nearby hatchery and wild populations generally have similar ocean distributions, these results likely reflect patterns for many populations not included. Combined, our results highlight the need to consider changes in body size and egg production when assessing the dynamics of anadromous fish populations and designing management or conservation plans, particularly for depressed populations.

Effects of a School-Based Garden Program on Academic Performance: A Cluster Randomized Controlled Trial - Jaimie N. Davis; Katie Nikah; Matthew J. Landry; Sarvenaz Vandyousefi; Reem Ghaddar; Matthew Jeans; Michele Hockett Cooper; Bonnie Martin; Lyndsey Waugh; Shreela V. Sharma; Alexandra E. van den Berg (Journal of the Academy of Nutrition and Dietetics, 2023)

Implementation of Additional Beta–Gamma Detectors for Improved Radioxenon Laboratory Throughput - Michael Foxe; Theodore Bowyer; Ian Cameron; Matthew Cooper; James Hayes; Lance Lidey; Michael Mayer; Jennifer Mendez; Johnathan Slack (Pure and Applied Geophysics, 2023)

Demonstration of low-level biogenic fuel content using quench curve and direct liquid scintillation counting (LSC) methods - Charles G. Doll; Andrew E. Plymale; Matthew J. O'Hara; Christopher J. Thompson; Alan Cooper; Huamin Wang; Mariefel V. Olarte (Fuel, 2023)

Monitoring threatened species with environmental DNA and open ecological data: Local distribution and habitat preferences of scalloped hammerhead sharks (Sphyrna lewini) - Alyssa M. Budd; Tom Schils; Madalyn K. Cooper; Mitchell B. Lyons; Matthew S. Mills; Mari E. Deinhart; Agnès Le Port; Roger Huerlimann; Jan M. Strugnell (Biological Conservation, 2023)

Profiling human pathogenic repeat expansion regions by synergistic and multi-level impacts on molecular connections - Cong Fan; Ken Chen; Yukai Wang; Edward V. Ball; Peter D. Stenson; Matthew Mort; Albino Bacolla; Hildegard Kehrer-Sawatzki; John A. Tainer; David N. Cooper; Huiying Zhao (Human Genetics, 2023)

Assay measurement of gaseous UF6 using femtosecond laser-induced breakdown spectroscopy in the 424.4 nm spectral region - Benjamin S. Jordan; Jason D. Readle; Jeffrey R. Cooper; Matthew Cook; Jason P. Hayward; J. Daniel Hartman; Dean Forrest; Howard L. Hall (Annals of Nuclear Energy, 2023)

Formation, remobilisation and alteration processes at inactive hydrothermal vents: insights from elemental analysis of Cu-(Fe-)S sulfides from TAG, Mid-Atlantic Ridge - Berit Lehrmann; Matthew J. Cooper; J. Andy Milton; Bramley J. Murton (Mineralium Deposita, 2022)

Age, growth and diet of crevalle jack ( Caranx hippos ) in the Gulf of Mexico - Amanda E. Jefferson; Matthew B. Jargowsky; Genevieve M. Ivec; Pearce T. Cooper; Jessica L. Carroll; Carissa L. Gervasi; Jennifer S. Rehage; John F. Mareska; Sean P. Powers; J. Marcus Drymon (Fisheries Management and Ecology, 2022)
The goals of this study were to generate baseline population dynamics parameters for Gulf of Mexico crevalle jack Caranx hippos and examine the foraging habits of Mississippi and Alabama crevalle jack. Specimens were collected from Mississippi, Alabama and Florida, and age was estimated from sagittal otoliths. Stomachs from some specimens were retained for dietary analyses. Age classes spanned 0–20 years. Overall growth was best represented by the logistic growth model, whereas sex‐specific growth was best represented by a version of the von Bertalanffy growth function that allowed L ∞ to vary by sex while holding k and t 0 constant between sexes. Fishes were more important to crevalle jack diet than invertebrates, and diet varied among locations and years. These findings will address fundamental knowledge gaps to inform age‐based stock assessments for crevalle jack and ecosystem approaches to fisheries management in the Gulf of Mexico.

Influences of seasonality and habitat quality on Great Lakes coastal wetland fish community composition and diets - Sara N. Diller; Anna M. Harrison; Kurt P. Kowalski; Valerie J. Brady; Jan J. H. Ciborowski; Matthew J. Cooper; Joshua D. Dumke; Joseph P. Gathman; Carl R. Ruetz; Donald G. Uzarski; Douglas A. Wilcox; Jeffrey S. Schaeffer (Wetlands Ecology and Management, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Post release monitoring of rehabilitated gray seal pups over large temporal and spatial scales - Sue Sayer; Rebecca Allen; Katie Bellman; Marion Beaulieu; Tamara Cooper; Natalie Dyer; Kirsten Hockin; Kate Hockley; Dan Jarvis; Grace Jones; Paul Oaten; Natalie Waddington; et al. (Marine Mammal Science, 2022)
Wildlife rescue and rehabilitation is used globally to aid the conservation and welfare of marine species, however, postrelease monitoring is challenging. Here, long‐term, regional postrelease monitoring provides feedback for rehabilitation centers for gray seals ( Halichoerus grypus ). Data from 1,094 rehabilitated gray seals over 19 years across the southwest UK were examined to assess postrelease survivorship and the impact of release site on movements and range. Using flipper tags combined with photo identification, 391 rehabilitated seals (35.7%) were resighted, including 188 seals (17.2%) that were traced back to a specific rehabilitated individual with release data. The maximum monitoring duration for a single rehabilitated seal was 17 years, although the majority (151/188; 80%) were sighted for less than 5 years and 80/188 (43%) were resighted for less than a year. Almost all 188 traced rehabilitated seals ( n = 176, 93.6%) visited the St Ives Bay Wild Site, yet only half had been released at the adjacent St Ives Bay Release Site. Rehabilitated seals had similar dispersal patterns to their wild conspecifics but over a smaller area. Once released, rehabilitated animals face the same threats as their wild counterparts.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Distinct patterns of resting-state connectivity in U.S. service members with mild traumatic brain injury versus posttraumatic stress disorder - Carissa L. Philippi; Carmen S. Velez; Benjamin S.C. Wade; Ann Marie Drennon; Douglas B. Cooper; Jan E. Kennedy; Amy O. Bowles; Jeffrey D. Lewis; Matthew W. Reid; Gerald E. York; Mary R. Newsome; Elisabeth A. Wilde; et al. (Brain Imaging and Behavior, 2021)

Design and Operation of the U.S. Radionuclide Noble Gas Laboratory for the CTBTO - Michael Foxe; Theodore Bowyer; Ian Cameron; Matthew Cooper; James Hayes; Derek Haas; Lance Lidey; Michael Mayer; Jennifer Mendez; Johnathan Slack (Pure and Applied Geophysics, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

The Human Gene Mutation Database (HGMD®): optimizing its use in a clinical diagnostic or research setting - Peter D. Stenson; Matthew Mort; Edward V. Ball; Molly Chapman; Katy Evans; Luisa Azevedo; Matthew Hayden; Sally Heywood; David S. Millar; Andrew D. Phillips; David N. Cooper (Human Genetics, 2020)
The Human Gene Mutation Database (HGMD ® ) constitutes a comprehensive collection of published germline mutations in nuclear genes that are thought to underlie, or are closely associated with human inherited disease. At the time of writing (June 2020), the database contains in excess of 289,000 different gene lesions identified in over 11,100 genes manually curated from 72,987 articles published in over 3100 peer-reviewed journals. There are primarily two main groups of users who utilise HGMD on a regular basis; research scientists and clinical diagnosticians. This review aims to highlight how to make the most out of HGMD data in each setting.

A Basin-Wide Survey of Coastal Wetlands of the Laurentian Great Lakes: Development and Comparison of Water Quality Indices - Anna M. Harrison; Alexander J. Reisinger; Matthew J. Cooper; Valerie J. Brady; Jan J. H. Ciborowski; Katherine E. O’Reilly; Carl R. Ruetz; Douglas A. Wilcox; Donald G. Uzarski (Wetlands, 2020)

Does rank rule? Rank-related grooming patterns in Nicobar long-tailed macaques Macaca fascicularis umbrosus - Partha Sarathi Mishra; Arijit Pal; Avadhoot D. Velankar; Honnavalli N. Kumara; Mewa Singh; Matthew Cooper (Primates, 2020)

Discerning the dietary habits of the smooth butterfly ray Gymnura lessae using two distinct methods, otolith identification and metagenetics - Matthew B. Jargowsky; Pearce T. Cooper; Matthew J. Ajemian; Michael E. Colvin; J. Marcus Drymon (Journal of Fish Biology, 2020)
Two different methods, metagenetics and free‐otolith identification, were used to identify prey in the stomach contents of 531 Gymnura lessae captured by trawling in Mobile Bay, Alabama 2016–2018. Both methods were found to produce analogous results and were therefore combined into a single complete dataset. All prey were teleosts; the families Sciaenidae and Engraulidae were the most important prey (prey specie index of relative importance 89.3% I PSRI ). Multivariate analyses indicated that the diet of G. lessae varied with sex and seasonality. Specifically, variability was probably due to morphologically larger females consuming larger teleost prey species compared with males, whereas seasonal variability was probably due to changes in the available prey community composition. The findings indicate that both metagenetics and free otolith identification, used independently or complementarily, offer robust means of characterising dietary habits for teleost‐specialised species such as G. lessae , which may play an important role in the structure and maintenance of coastal food webs such as those in Mobile Bay.

Leveraging a Landscape-Level Monitoring and Assessment Program for Developing Resilient Shorelines throughout the Laurentian Great Lakes - Donald G. Uzarski; Douglas A. Wilcox; Valerie J. Brady; Matthew J. Cooper; Dennis A. Albert; Jan J. H. Ciborowski; Nicholas P. Danz; Anne Garwood; Joseph P. Gathman; Thomas M. Gehring; Greg P. Grabas; Robert W. Howe; et al. (Wetlands, 2019)

What can cetacean stranding records tell us? A study of UK and Irish cetacean diversity over the past 100 years - Ellen J. Coombs; Rob Deaville; Richard C. Sabin; Louise Allan; Mick O'Connell; Simon Berrow; Brian Smith; Andrew Brownlow; Mariel Ten Doeschate; Rod Penrose; Ruth Williams; Matthew W. Perkins; et al. (Marine Mammal Science, 2019)
There are many factors that may explain why cetaceans (whales, dolphins, and porpoises) strand. Around the UK and Ireland, over 20,000 stranding records have been collected since 1913, resulting in one of the longest, continuous, systematic stranding data sets in the world. We use this data set to investigate temporal and spatial trends in cetacean strandings and use generalized additive models (GAMs) to investigate correlates of strandings. We find a dramatic increase in strandings since the 1980s, most likely due to increases in recording effort, and the formation of formal strandings networks. We found no correlation between the numbers of cetaceans stranding each year and several potential environmental and anthropogenic predictors: storms, geomagnetic activity, North Atlantic Oscillations, sea‐surface temperature, and fishing catch. We suggest that this is because the scale of change in the variables is too coarse to detect any potential correlations. It may also highlight the idiosyncratic nature of species’ responses to external pressures, and further the need to investigate other potential correlates of strandings, such as bycatch and military sonar. Long‐term cetacean stranding data provide vital information on past and present diversity for common, rare, and inconspicuous species. This study underlines the importance of continued support for stranding networks.

Relationships between the distribution and abundance of the invasive faucet snail (Bithynia tentaculata) and environmental factors in Laurentian Great Lakes coastal wetlands - Neil T. Schock; Alexander J. Reisinger; Lindsey S. Reisinger; Matthew J. Cooper; Jan J. H. Cibrowski; Thomas M. Gehring; Ashley H. Moerke; Carl R. Ruetz; Donald G. Uzarski (Biological Invasions, 2019)

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

Subcortical shape and neuropsychological function among U.S. service members with mild traumatic brain injury - David F. Tate; Benjamin S. C. Wade; Carmen S. Velez; Ann Marie Drennon; Jacob D. Bolzenius; Douglas B. Cooper; Jan E. Kennedy; Matthew W. Reid; Amy O. Bowles; Paul M. Thompson; Boris A. Gutman; Jeffrey D. Lewis; et al. (Brain Imaging and Behavior, 2019)

Trace elements and isotope data of the Um Garayat gold deposit, Wadi Allaqi district, Egypt - Basem Zoheir; Ashraf Emam; Iain K. Pitcairn; Arman Boskabadi; Yann Lehaye; Matthew J. Cooper (Mineralium Deposita, 2019)

Unravelling the complexity of magma plumbing at Mount St. Helens: a new trace element partitioning scheme for amphibole - Madeleine C. S. Humphreys; George F. Cooper; Jing Zhang; Matthew Loewen; Adam J. R. Kent; Colin G. Macpherson; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2019)

What can seabirds tell us about the tide? - Matthew Cooper; Charles Bishop; Matthew Lewis; David Bowers; Mark Bolton; Ellie Owen; Stephen Dodd (Ocean Science, 2018)
Small global positioning system (GPS) trackers are now routinely used to study the movement and behaviour of birds at sea. If the birds rest on the water they become “drifters of opportunity” and can be used to give information about surface currents. In this paper, we use a small data set from satellite-tracked razorbills (Alca torda) in the Irish Sea to test the potential of this idea for measuring tidal currents. Razorbills regularly rest on the sea overnight and their tracks at this time are consistent with their drifting with the tidal flows and changing direction as the flood turns to ebb and vice versa. Data from 4 years (2011–2014) have been binned in a geographical grid and analysed to give the variation of current over a mean tidal cycle in each grid element. A map of maximum current speed is consistent with a numerical model of the tidal currents in the region. The root mean square difference between observed maximum speed and that predicted by the model is 0.15 m s−1, about 15 % of typical current speeds in the area. The divergence between bird-track speed and model prediction increases in regions of the fastest tidal currents. The method clearly has its limitations, but the results of this study show that tagged birds resting on the sea have potential to provide relatively inexpensive quantitative information about surface tidal currents over an extended geographical area.

Utilization of Low Grade Wood for Use as Animal Bedding: A Case Study of Eastern Hemlock - Matthew M Smith; Cooper J Park; Cheryl P Andam; John D Aber (Journal of Forestry, 2018)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

An expanded fish-based index of biotic integrity for Great Lakes coastal wetlands - Matthew J. Cooper; Gary A. Lamberti; Ashley H. Moerke; Carl R. Ruetz; Douglas A. Wilcox; Valerie J. Brady; Terry N. Brown; Jan J. H. Ciborowski; Joseph P. Gathman; Greg P. Grabas; Lucinda B. Johnson; Donald G. Uzarski (Environmental Monitoring and Assessment, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Pharmacological inhibition of the NLRP3 inflammasome as a potential target for multiple sclerosis induced central neuropathic pain - Nemat Khan; Andy Kuo; David A. Brockman; Matthew A. Cooper; Maree T. Smith (Inflammopharmacology, 2018)

Soil nutrient maps of Sub-Saharan Africa: assessment of soil nutrient content at 250 m spatial resolution using machine learning - Tomislav Hengl; Johan G. B. Leenaars; Keith D. Shepherd; Markus G. Walsh; Gerard B. M. Heuvelink; Tekalign Mamo; Helina Tilahun; Ezra Berkhout; Matthew Cooper; Eric Fegraus; Ichsani Wheeler; Nketia A. Kwabena (Nutrient Cycling in Agroecosystems, 2017)

regSNPs-splicing: a tool for prioritizing synonymous single-nucleotide substitution - Xinjun Zhang; Meng Li; Hai Lin; Xi Rao; Weixing Feng; Yuedong Yang; Matthew Mort; David N. Cooper; Yue Wang; Yadong Wang; Clark Wells; Yaoqi Zhou; et al. (Human Genetics, 2017)

Local genes for local bacteria: Evidence of allopatry in the genomes of transatlantic Campylobacter populations - Ben Pascoe; Guillaume Méric; Koji Yahara; Helen Wimalarathna; Susan Murray; Matthew D. Hitchings; Emma L. Sproston; Catherine D. Carrillo; Eduardo N. Taboada; Kerry K. Cooper; Steven Huynh; Alison J. Cody; et al. (Molecular Ecology, 2017)
The genetic structure of bacterial populations can be related to geographical locations of isolation. In some species, there is a strong correlation between geographical distance and genetic distance, which can be caused by different evolutionary mechanisms. Patterns of ancient admixture in Helicobacter pylori can be reconstructed in concordance with past human migration, whereas in Mycobacterium tuberculosis it is the lack of recombination that causes allopatric clusters. In Campylobacter , analyses of genomic data and molecular typing have been successful in determining the reservoir host species, but not geographical origin. We investigated biogeographical variation in highly recombining genes to determine the extent of clustering between genomes from geographically distinct Campylobacter populations. Whole‐genome sequences from 294 Campylobacter isolates from North America and the UK were analysed. Isolates from within the same country shared more recently recombined DNA than isolates from different countries. Using 15 UK /American closely matched pairs of isolates that shared ancestors, we identify regions that have frequently and recently recombined to test their correlation with geographical origin. The seven genes that demonstrated the greatest clustering by geography were used in an attribution model to infer geographical origin which was tested using a further 383 UK clinical isolates to detect signatures of recent foreign travel. Patient records indicated that in 46 cases, travel abroad had occurred UK origin. Identification of biogeographical markers in Campylobacter genomes will contribute to improved source attribution of clinical Campylobacter infection and inform intervention strategies to reduce campylobacteriosis.

The Human Gene Mutation Database: towards a comprehensive repository of inherited mutation data for medical research, genetic diagnosis and next-generation sequencing studies - Peter D. Stenson; Matthew Mort; Edward V. Ball; Katy Evans; Matthew Hayden; Sally Heywood; Michelle Hussain; Andrew D. Phillips; David N. Cooper (Human Genetics, 2017)

Genetic dissection of sorghum grain quality traits using diverse and segregating populations - Richard E. Boyles; Brian K. Pfeiffer; Elizabeth A. Cooper; Bradley L. Rauh; Kelsey J. Zielinski; Matthew T. Myers; Zachary Brenton; William L. Rooney; Stephen Kresovich (Theoretical and Applied Genetics, 2017)

Carbonate alteration of ophiolitic rocks in the Arabian–Nubian Shield of Egypt: sources and compositions of the carbonating fluid and implications for the formation of Au deposits - Arman Boskabadi; Iain K. Pitcairn; Curt Broman; Adrian Boyce; Damon A. H. Teagle; Matthew J. Cooper; Mokhles K. Azer; Robert J. Stern; Fathy H. Mohamed; Jaroslaw Majka (International Geology Review, 2017)

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

Body burdens of heavy metals in Lake Michigan wetland turtles - Dayna L. Smith; Matthew J. Cooper; Jessica M. Kosiara; Gary A. Lamberti (Environmental Monitoring and Assessment, 2016)

Conservation implications of omitting historical data sources: response to Baisre - Loren McClenachan; Andrew B. Cooper; Marah Hardt; Matthew McKenzie; Joshua A. Drew (Conservation Biology, 2016)

The metabolic rate of cultured muscle cells from hybrid Coturnix quail is intermediate to that of muscle cells from fast-growing and slow-growing Coturnix quail - Clara Cooper-Mullin; Ana Gabriela Jimenez; Nicholas B. Anthony; Matthew Wortman; Joseph B. Williams (Journal of Comparative Physiology B, 2015)

Stochastic dynamics of a warmer Great Barrier Reef - Jennifer K. Cooper; Matthew Spencer; John F. Bruno (Ecology, 2015)
Pressure on natural communities from human activities continues to increase. Even unique ecosystems like the Great Barrier Reef (GBR), that until recently were considered near‐pristine and well‐protected, are showing signs of rapid degradation. We collated recent (1996–2006) spatiotemporal relationships between benthic community composition on the GBR and environmental variables (ocean temperature and local threats resulting from human activity). We built multivariate models of the effects of these variables on short‐term dynamics, and developed an analytical approach to study their long‐term consequences. We used this approach to study the effects of ocean warming under different levels of local threat. Observed short‐term changes in benthic community structure (e.g., declining coral cover) were associated with ocean temperature (warming) and local threats. Our model projected that, in the long term, coral cover of less than 10% was not implausible. With increasing temperature and/or local threats, corals were initially replaced by sponges, gorgonians, and other taxa, with an eventual moderately high probability of domination (>50%) by macroalgae when temperature increase was greatest (e.g., 3.5°C of warming). Our approach to modeling community dynamics, based on multivariate statistical models, enabled us to project how environmental change (and thus local and international policy decisions) will influence the future state of coral reefs. The same approach could be applied to other systems for which time series of ecological and environmental variables are available.

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

Dispersal Mode and Ability Affect the Spatial Turnover of a Wetland Macroinvertebrate Metacommunity - Christopher J. Patrick; Matthew J. Cooper; Donald G. Uzarski (Wetlands, 2014)

Pharmacokinetics and Pharmacodynamics of CD4-Anchoring Bi-Functional Fusion Inhibitor in Monkeys - Xingrong Liu; Ying C. Ou; Jun Zhang; Ago Ahene; Douglas Clark; Su-Chun Hsieh; Matthew Cooper; Changhua Ji (Pharmaceutical Research, 2014)

The Human Gene Mutation Database: building a comprehensive mutation repository for clinical and molecular genetics, diagnostic testing and personalized genomic medicine - Peter D. Stenson; Matthew Mort; Edward V. Ball; Katy Shaw; Andrew D. Phillips; David N. Cooper (Human Genetics, 2014)
The Human Gene Mutation Database (HGMD ® ) is a comprehensive collection of germline mutations in nuclear genes that underlie, or are associated with, human inherited disease. By June 2013, the database contained over 141,000 different lesions detected in over 5,700 different genes, with new mutation entries currently accumulating at a rate exceeding 10,000 per annum. HGMD was originally established in 1996 for the scientific study of mutational mechanisms in human genes. However, it has since acquired a much broader utility as a central unified disease-oriented mutation repository utilized by human molecular geneticists, genome scientists, molecular biologists, clinicians and genetic counsellors as well as by those specializing in biopharmaceuticals, bioinformatics and personalized genomics. The public version of HGMD ( https://www.hgmd.cf.ac.uk ) is freely available to registered users from academic institutions/non-profit organizations whilst the subscription version (HGMD Professional) is available to academic, clinical and commercial users under license via BIOBASE GmbH.

Magnitude and time course of changes in maximal oxygen uptake in response to distinct regimens of chronic interval training in sedentary women - Todd A. Astorino; Matthew M. Schubert; Elyse Palumbo; Douglas Stirling; David W. McMillan; Christina Cooper; Jackie Godinez; Donovan Martinez; Rachael Gallant (European Journal of Applied Physiology, 2013)

Influence of geomorphic setting on the metabolism of Lake Huron fringing wetlands - Matthew J. Cooper; Alan D. Steinman; Donald G. Uzarski (Limnology and Oceanography, 2013)
We measured gross primary productivity (GPP) and respiration (R) seasonally in benthic, water column, and epiphytic microhabitats of Lake Huron fringing wetlands. Spring areal GPP ranged from 33 to 103 mmol O 2 m −2 d −1 , spring R ranged from 16 to 110 mmol O 2 m −2 d −1 , and the water column was the most important microhabitat for both GPP and R on average. Summer GPP ranged from 40 to 131 mmol O 2 m −2 d −1 , R ranged from 25 to 155 mmol O 2 m −2 d −1 , and the water column and benthic microhabitats were equally important for GPP and R. Fall GPP ranged from 2 m −2 d −1 , and R ranged from 2 m −2 d −1 , with the benthic and water column microhabitats being equally important. Net metabolism (the difference between GPP and R) was close to zero at most wetlands, but when macrophyte productivity was accounted for, most wetlands appeared autotrophic. Both GPP and R were highest in deep wetlands protected from hydrologic energy and declined with increasing wave exposure. With increasing exposure, wetlands were restricted to shallower water and benthic GPP and R increased relative to water column GPP and R. This pattern persisted to intermediate levels of exposure, beyond which benthic GPP and R declined as a result of physical disturbance to the sediment. Coastal wetlands are hotspots of productivity in Lake Huron and hydrologic energy is an important driver of total metabolism rates, as well as the distribution of GPP and R among microhabitats.

Assessing vulnerability due to sea-level rise in Maui, Hawai‘i using LiDAR remote sensing and GIS - Hannah M. Cooper; Qi Chen; Charles H. Fletcher; Matthew M. Barbee (Climatic Change, 2013)

Natural History Traits Associated with Detecting Mortality Within Residential Bird Communities: Can Citizen Science Provide Insights? - Caren Beth Cooper; Kerrie Anne Therese Loyd; Tessa Murante; Matthew Savoca; Janis Dickinson (Environmental Management, 2012)

Ecological risk assessment of multiple hatchery programs in the upper Columbia watershed using Delphi and modeling approaches - Todd N. Pearsons; Andrew R. Murdoch; Greg Mackey; Keely G. Murdoch; Tracy W. Hillman; Matthew R. Cooper; Joseph L. MIller (Environmental Biology of Fishes, 2012)

Chemical and physical factors associated with yellow perch abundance in Great Lakes coastal wetlands: patterns within and among wetland types - Aaron D. Parker; Matthew J. Cooper; Carl R. Ruetz; David P. Coulter; Donald G. Uzarski (Wetlands Ecology and Management, 2012)

Great Lakes coastal wetland habitat use by seven turtle species: influences of wetland type, vegetation, and abiotic conditions - Alex C. Wieten; Matthew J. Cooper; Aaron D. Parker; Donald G. Uzarski (Wetlands Ecology and Management, 2012)

Alarm Pheromones Do Not Mediate Rapid Shifts in Honey Bee Guard Acceptance Threshold - Margaret J. Couvillon; Sarah N. Barton; Jennifer A. Cohen; Onna K. Fabricius; Martin H. Kärcher; Lee S. Cooper; Matthew J. Silk; Heikki Helanterä; Francis L. W. Ratnieks (Journal of Chemical Ecology, 2010)

Sedimentation of acantharian cysts in the Iceland Basin: Strontium as a ballast for deep ocean particle flux, and implications for acantharian reproductive strategies - Patrick Martin; John T. Allen; Matthew J. Cooper; David G. Johns; Richard S. Lampitt; Richard Sanders; Damon A. H. Teagle (Limnology and Oceanography, 2010)
Acantharian cysts were discovered in sediment trap samples from spring 2007 at 2000 m in the Iceland Basin. Although these single‐celled organisms contribute to particulate organic matter flux in the upper mesopelagic, their contribution to bathypelagic particle flux has previously been found negligible. Four time‐series sediment traps were deployed and all collected acantharian cysts, which are reproductive structures. Across all traps, cysts contributed on average 3–22%, and 4–24% of particulate organic carbon and nitrogen (POC and PON) flux, respectively, during three separate collection intervals (the maximum contribution in any one trap was 48% for POC and 59% for PON). Strontium (Sr) flux during these 6 weeks reached 3 mg m −2 d −1 . The acantharian celestite (SrSO 4 ) skeleton clearly does not always dissolve in the mesopelagic as often thought, and their cysts can contribute significantly to particle flux at bathypelagic depths during specific flux events. Their large size (~ 1 mm) and mineral ballast result in a sinking rate of ~ 500 m d −1 ; hence, they reach the bathypelagic before dissolving. Our findings are consistent with a vertical profile of salinity‐normalized Sr concentration in the Iceland Basin, which shows a maximum at 1700 m. Profiles of salinity‐normalized Sr concentration in the subarctic Pacific reach maxima at ≤ 1500 m, suggesting that Acantharia might contribute to the bathypelagic particle flux there as well. We hypothesize that Acantharia at high latitudes use rapid, deep sedimentation of reproductive cysts during phytoplankton blooms so that juveniles can exploit the large quantity of organic matter that sinks rapidly to the deep sea following a bloom.

REE and Sr isotope characteristics of carbonate within the Cu–Co mineralized sedimentary sequence of the Nchanga Mine, Zambian Copperbelt - Stephen Roberts; Martin R. Palmer; Matthew J. Cooper; Peter Buchaus; Drew Sargent (Mineralium Deposita, 2009)

The potential impacts of sea level rise on the coastal region of New Jersey, USA - Matthew J. P. Cooper; Michael D. Beevers; Michael Oppenheimer (Climatic Change, 2008)

Evaluating Dominance Styles in Assamese and Rhesus Macaques - Matthew A. Cooper; Irwin S. Bernstein (International Journal of Primatology, 2008)

Macroinvertebrate community composition in relation to anthropogenic disturbance, vegetation, and organic sediment depth in four Lake Michigan drowned river-mouth wetlands - Matthew J. Cooper; Donald G. Uzarski; Thomas M. Burton (Wetlands, 2007)

Corticotropin-releasing factor receptors in the dorsal raphe nucleus modulate social behavior in Syrian hamsters - Matthew A. Cooper; Kim L. Huhman (Psychopharmacology, 2007)

Vomiting in Wild Bonnet Macaques - Elizabeth C. Johnson; Eric Hill; Matthew A. Cooper (International Journal of Primatology, 2007)

Male Influx, Infanticide, and Female Transfer in Macaca radiata radiata - Mewa Singh; H. N. Kumara; M. Ananda Kumar; Mridula Singh; Matthew Cooper (International Journal of Primatology, 2006)

Effect of Dominance, Reproductive State, and Group Size on Body Mass in Macaca radiata - Matthew A. Cooper; M. S. Chaitra; Mewa Singh (International Journal of Primatology, 2004)

Linkage and association mapping of the LRP5 locus on chromosome 11q13 in type 1 diabetes - Rebecca C. J. Twells; Charles A. Mein; Felicity Payne; Riitta Veijola; Matthew Gilbey; Matthew Bright; Andrew Timms; Yusuke Nakagawa; Hywel Snook; Sarah Nutland; Helen E. Rance; Philippa Carr; et al. (Human Genetics, 2003)

Integration of New Males into Four Social Groups of Tufted Capuchins (Cebus apella) - Matthew A. Cooper; Irwin S. Bernstein; Dorothy M. Fragaszy; Frans B. M. de Waal (International Journal of Primatology, 2001)

Discrimination between related and unrelated individuals in the Australian lizard Egernia striolata - Michael Bull; Clare Griffin; Matthew Bonnett; Michael Gardner; Steven Cooper (Behavioral Ecology and Sociobiology, 2001)

Integrated models of livestock systems for climate change studies. 2. Intensive systems - J. R. Turnpenny; D. J. Parsons; A. C. Armstrong; J. A. Clark; K. Cooper; A. M. Matthews (Global Change Biology, 2001)
Summary The potential impact of climate change by the year 2050 on intensive livestock systems in Britain is assessed through the use of simulation models of farming systems. The submodels comprise livestock feeding, livestock thermal balance and the thermal balance of controlled environment buildings and a stochastic weather generator. These are integrated to form system models for growing pigs and broiler chickens. They are applied to scenarios typical of SE England, which is the warmest region of the country and represents the worst case. For both species the frequency of severe heat stress is substantially increased, with a consequent risk of mortality. To offset this, it would be necessary to reduce stocking densities considerably, or to invest in improved ventilation or cooling equipment. Other effects on production are likely to be small.

Integrated models of livestock systems for climate change studies. 1. Grazing systems - D. J. Parsons; A. C. Armstrong; J. R. Turnpenny; A. M. Matthews; K. Cooper; J. A. Clark (Global Change Biology, 2001)
Summary The potential impact of climate change by the year 2050 on British grazing livestock systems is assessed through the use of simulation models of farming systems. The submodels, consisting of grass production, livestock feeding, livestock thermal balance, the thermal balance of naturally ventilated buildings and a stochastic weather generator, are described. These are integrated to form system models for sheep, beef calves and dairy cows. They are applied to scenarios representing eastern (dry) lowlands, western (wet) lowlands and uplands. The results show that such systems should be able to adapt to the expected climatic changes. There is likely to be a small increase in grass production, possibly allowing an increase in total productivity in some cases.

Temporal distribution of waterfowl in eastern South Dakota: Implications for aerial surveys - David E. Naugle; Rex R. Johnson; Thomas R. Cooper; Matthew M. Holland; Kenneth F. Higgins (Wetlands, 2000)